Confessional conversions on the territory of Belarus in the second half of the 19th – early 20th century: overview of historiography - Karol, Marharyta M. (Journal of the Belarusian State University. History, 2021)
The article examines the stages of the formation of historiography devoted to the problems of confessional conversions in the second half of the 19th century on the territory of the Belarusian provinces. The historiographic trends that formed from the end of the 19th century to the beginning of the 21st century were identified and analysed. The authour studies the peculiarities of Belarusian and foreign historiography at the present stage, when a large number of works on religious issues has appeared, including confessional conversions. It is argued that in Soviet times, the issue of transitions from Catholicism to Orthodoxy was practically not touched upon. In their approaches and assessments, some researchers continue the traditions of pre-revolutionary historiography, but the majority of modern scientists strive to give an objective picture of religious processes on the Belarusian lands, to show them in the context of general state policy. The relevance of the article is due to the coverage of various points of view on the problem of confessional conversions. It is noted that pre-revolutionary researchers, first of all, sought to prove the voluntariness of conversions to Orthodoxy, but during this period, works were also created in which this thesis was questioned.
Keywords: historiography; religion; confessional conversions; Russian Empire